A landscape of conflict? : rural fortifications in the Argolid (400-146 BC) - Blomley, Anna Magdalena, 1991- (Archaeopress Archaeology, 2022)
This is a systematic study of Late Classical and Hellenistic rural fortifications in ancient Argos and the city-states of the Argolic Akte. Based on one of the largest regional corpora of Greek fortified sites, the volume investigates the function of rural fortifications by placing them in the context of their surrounding landscape.